Evolution of design for sustainability: From product design to design for system innovations and transitions - Ceschin, Fabrizio; Gaziulusoy, Idil (Design studies, 2016)
The paper explores the evolution of Design for Sustainability (DfS). Following a quasi-chronological pattern, our exploration provides an overview of the DfS field, categorising the design approaches developed in the past decades under four innovation levels: Product, Product-Service System, Spatio-Social and Socio-Technical System. As a result, we propose an evolutionary framework and map the reviewed DfS approaches onto this framework. The proposed framework synthesizes the evolution of the DfS field, showing how it has progressively expanded from a technical and product-centric focus towards large scale system level changes in which sustainability is understood as a socio-technical challenge. The framework also shows how the various DfS approaches contribute to particular sustainability aspects and visualises linkages, overlaps and complementarities between these approaches. •A review of historical evolution of Design for Sustainability is provided.•A framework that synthesis the evolution of Design for Sustainability is proposed.•DfS has expanded from a product focus towards a socio-technical system focus.•Linkages, overlaps and complementarities between DfS approaches are identified.